The Role of Banking in Implementation and Information Provision of People's Business Credit - Ahmad Nur Budi Utama; Ade Irma Suryani (Jurnal Smart: Sosial Ekonomi Kerakyatan, 2023)
One way to measure the economic progress of a country is to look at the people's business fields. The field refers to the economic sector which includes various types of businesses run by micro, small and medium entrepreneurs (MSMEs) who work independently or in groups. To help small businesses facing capital problems, the government encourages banks to provide business capital with the aim of accelerating economic growth, increasing competitiveness, and creating jobs. The People's Business Credit is one of the programs issued by the government to help small communities who have problems with capital. How does people's business credit help MSMEs? This study used a qualitative approach with secondary data. BNI KUR provides a credit ceiling that allows people to take advantage of it when they plan and develop their business. This research also discusses how BNI KUR plays a role for micro and small businesses that want to develop their business by providing working capital loans and investment loans.